Endoscopic Vacuum-assisted Closure in a Patient with an Overtube-induced Esophageal Perforation - Yuri Kim; Seokin Kang; Ji Yong Ahn (Yong Chan Lee, 2021)
An esophageal perforation is one of the most fatal clinical events, with a mortality rate of up to 21%. This may arise postoperatively or post-endoscopically. In the past, surgical treatment, such as an esophagectomy, was performed these cases. However, the procedure was challenging and had a high risk of postoperative complications. Recently, advancements in endoscopic techniques have been made, and endoscopic procedures became a common treatment modality for patients with esophageal perforation, even in those with underlying diseases. Among the endoscopic procedures, endoscopic vacuum-assisted closure (E-VAC) has been known to be safe and effective. We present the case of a 64-year-old female with advanced liver cirrhosis and an overtube-induced esophageal perforation during esophageal variceal ligation. She was successfully treated with E-VAC.